A Quality Improvement Plan for Implementing an Innovative Organization System for Pediatric Airway Patients - Kerns, Aileen K.; Mahoney, Rebecca; Deeds, Kathryn; Boone-Edwards, Keshia; Ross, Mary; Siegel, Bianca (Journal of Pediatric Intensive Care, 2020)
Risks of pediatric tracheostomy are well known. The objectives of this quality improvement study were to organize tracheostomy supplies into a comprehensive care kit and demonstrate that the kits improved nursing and parental comfort in providing tracheostomy care routinely and emergently. Kits were assembled using roll-up toiletry style bags and organized in a uniform fashion with necessary supplies. Nurses and parents were surveyed using a 5-point Likert-type. Feedback was overall very positive; the kits were found to ease the transition of caring for a child with a new tracheostomy from hospital to home. This intervention can easily be adapted at other pediatric institutions.
Keywords: pediatrics; tracheostomy; safety